2017
DOI: 10.3168/jds.2016-11427
|View full text |Cite
|
Sign up to set email alerts
|

Variation in fat globule size in bovine milk and its prediction using mid-infrared spectroscopy

Abstract: The objectives of this study were to investigate the sources of variation in milk fat globule (MFG) size in bovine milk and its prediction using mid-infrared (MIR) spectroscopy. Mean MFG size was measured in 2,076 milk samples from 399 Ayrshire, Brown Swiss, Holstein, and Jersey cows, and expressed as volume moment mean (D[4,3]) and surface moment mean (D[3,2]). The mid-infrared spectra of the samples and milk performance data were also recorded during routine milk recording and testing. The effects of breed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 24 publications
6
40
0
Order By: Relevance
“…The considerable variation in average MFG size between individual cows is in accordance with previous studies investigating the MFG size distribution within a herd (Logan et al, 2014) or across several herds (Fleming et al, 2017). Logan et al (2014) measured the MFG size distribution within the herd once in spring and twice in autumn over two consecutive years and the average MFG sizes ranged between 2.5 and 5.7 µm.…”
Section: Milk Fat Globule Sizesupporting
confidence: 88%
See 3 more Smart Citations
“…The considerable variation in average MFG size between individual cows is in accordance with previous studies investigating the MFG size distribution within a herd (Logan et al, 2014) or across several herds (Fleming et al, 2017). Logan et al (2014) measured the MFG size distribution within the herd once in spring and twice in autumn over two consecutive years and the average MFG sizes ranged between 2.5 and 5.7 µm.…”
Section: Milk Fat Globule Sizesupporting
confidence: 88%
“…A similar effect of parity on MFG size was previously shown in ewes, with first parity animals producing milk with smaller average MFG size (Martini et al, 2004). Conversely, a recent study by Fleming et al (2017) showed no significant impact of parity on MFG size distribution in dairy cows. This extensive study also investigated additive effects of several physiological and environmental variables on MFG size using a linear mixed model.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…The MIR spectroscopy associated with chemometry has been successfully applied to predict the chemical composition (sugars, organic acids, acidity, dry matter, polyphenols, proteins, humidity, fats, micronutrients, etc.) of various food products, such as: mango juice [9], apple juice [10], or even the whole fruit of apricots [11], or tomatoes [12], wine [13,14], honey [15], leaves and trunk of vine [16], pomegranates [17][18][19], grapes [20], wheat [21], milk [22], lemon [23], black beans [24] and chocolate [25]. The use of FT-MIR for the prediction of sucrose, glucose and fructose was also confirmed by Karoui [26] for plums and by Mureşan [27] for the apple fruit, together with linear discriminant analysis, principal component (PCR) and partial least squares (PLS) regressions.…”
Section: Introductionmentioning
confidence: 99%